2000
DOI: 10.1038/35041603
|View full text |Cite
|
Sign up to set email alerts
|

A transcription reinitiation intermediate that is stabilized by activator

Abstract: High levels of gene transcription by RNA polymerase II depend on high rates of transcription initiation and reinitiation. Initiation requires recruitment of the complete transcription machinery to a promoter, a process facilitated by activators and chromatin remodelling factors. Reinitiation probably occurs through a different pathway. After initiation, a subset of the transcription machinery remains at the promoter, forming a platform for assembly of a second transcription complex. Here we describe the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
349
5
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(386 citation statements)
references
References 27 publications
29
349
5
3
Order By: Relevance
“…This finding suggests that CR3 may function in part by holding the Mediator at the promoter following each round of transcription initiation and the required disassembly of the PIC. This mechanism has been suggested to stimulate the rate of transcription reinitiation by the strong VP16 AD (Yudkovsky et al, 2000). In addition, the studies with ELK1 suggest that an interaction with MED23 stimulates PIC initiation.…”
Section: E1a Conserved Region 3 Activation Of Early Viral Gene Expresmentioning
confidence: 94%
“…This finding suggests that CR3 may function in part by holding the Mediator at the promoter following each round of transcription initiation and the required disassembly of the PIC. This mechanism has been suggested to stimulate the rate of transcription reinitiation by the strong VP16 AD (Yudkovsky et al, 2000). In addition, the studies with ELK1 suggest that an interaction with MED23 stimulates PIC initiation.…”
Section: E1a Conserved Region 3 Activation Of Early Viral Gene Expresmentioning
confidence: 94%
“…High-resolution crystal structures have elucidated the TFIIB-TBP-DNA and RNAP II complexes, but little is known about TFIIB before it is incorporated into this complex (Hampsey, 1998;Hahn, 2004). It is thought that with each round of transcription TFIIB does not remain bound to the promoter, suggesting that the study of the import of new TFIIB may be relevant to transcription (Yudkovsky et al, 2000). Here we identify the import pathway of Sua7p, the yeast version of TFIIB.…”
Section: Introductionmentioning
confidence: 94%
“…Previously it was shown that PIC assembly occurs in at least three stages in this in vitro system, with TFIID and TFIIA recruited first to the promoter; TFIIB, Pol II, TFIIF, Mediator, and TFIIE recruited cooperatively in the next step; and TFIIH binding last (Ranish et al 1999;Yudkovsky et al 2000). PICs were assembled on immobilized templates by using ex- Interactions among SAGA, TFIIA, and TBP tracts containing conditional mutations in TBP, TFIIB, Mediator, or TFIIH (Fig.…”
Section: Identification Of Polypeptides That Cross-link To the Tfiia Ntdmentioning
confidence: 99%